2021
DOI: 10.1038/s42003-021-01904-w
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a major surface antigen SAG19 from Eimeria tenella unifies the Eimeria SAG family

Abstract: In infections by apicomplexan parasites including Plasmodium, Toxoplasma gondii, and Eimeria, host interactions are mediated by proteins including families of membrane-anchored cysteine-rich surface antigens (SAGs) and SAG-related sequences (SRS). Eimeria tenella causes caecal coccidiosis in chickens and has a SAG family with over 80 members making up 1% of the proteome. We have solved the structure of a representative E. tenella SAG, EtSAG19, revealing that, despite a low level of sequence similarity, the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…SAGs in Eimeria are different than the predominant surface antigens families in the apicomplexans Toxoplasma and Plasmodium [12]. Also, a recent study showed that a fold within a representative SAG B subfamily protein in E. tenella are distinct from surface antigens of Toxoplasma and Plasmodium, and that this fold defines other Eimeria SAG sub-families [118]. Furthermore, this fold is conserved in Eimeria and C. cayetanensis and unrelated to SAGs or SRS proteins in other cyst-forming coccidia.…”
Section: Transcripts Characteristic Of Mature Oocystsmentioning
confidence: 99%
“…SAGs in Eimeria are different than the predominant surface antigens families in the apicomplexans Toxoplasma and Plasmodium [12]. Also, a recent study showed that a fold within a representative SAG B subfamily protein in E. tenella are distinct from surface antigens of Toxoplasma and Plasmodium, and that this fold defines other Eimeria SAG sub-families [118]. Furthermore, this fold is conserved in Eimeria and C. cayetanensis and unrelated to SAGs or SRS proteins in other cyst-forming coccidia.…”
Section: Transcripts Characteristic Of Mature Oocystsmentioning
confidence: 99%
“…One recent analysis that utilized the ASSAM server for substructure searching in such a way was the discovery of a four aspartates arrangement (4D motif) that is involved in binding a divalent metal ion to stabilize the acetylcholinesterase of Torpedo californica ( 30 ). Another example had used ASSAM to identify a 3D motif that could be regarded as a fingerprint for the fold of a protein superfamily ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genome annotation has revealed that pathogenic eimerian can have up to 105 sags and species with severe pathologies may have a higher number [ 46 ]. Over 80 sags have been identified to constitute about 1% of E. tenella proteome [ 59 ]. However, heterogeneity or nucleotide diversity of protein genes could vary in different isolates [ 60 ].…”
Section: A Glimpse Into Protein Gene Profilesmentioning
confidence: 99%
“…Currently, Emerian merozoites have about 47 SAGs whereas only 4 SAGs have been reported in the sporozoite of E. tenella [71] (Table 1). Eimeria tenella merozoite SAG, SAG 2, 4 and 19 are localised by a phospholipid anchor on the parasite surface membrane with variations in immunogenicity and abundance [59,111]. Nevertheless, Eimeria SAGs have significant homology with conserved surface antigens of C. cayetanensis [59].…”
Section: Eimeria Surface Proteinsmentioning
confidence: 99%